2017
DOI: 10.1038/s41598-017-04287-3
|View full text |Cite
|
Sign up to set email alerts
|

Multiple thermal spin transport performances of graphene nanoribbon heterojuction co-doped with Nitrogen and Boron

Abstract: Graphene nanoribbon is a popular material in spintronics owing to its unique electronic properties. Here, we propose a novel spin caloritronics device based on zigzag graphene nanoribbon (ZGNR), which is a heterojunction consisting of a pure single-hydrogen-terminated ZGNR and one doped with nitrogen and boron. Using the density functional theory combined with the non-equilibrium Green’s function, we investigate the thermal spin transport properties of the heterojunction under different magnetic configurations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“… 23,24 In a recent study, Huang et al assayed the thermal spin-transport properties of hybrid boron, nitrogen co-doped ZGNR under various magnetic configurations. 25 In a combined experimental and theoretical study, Makarova et al ascertained the strongly coupled magnetic states at the graphene–fluorographene interface from magnetic susceptibility measurements. 26 Subsequently, Chen et al impressively demonstrated the effect of metal substrates on the local magnetic moments of zigzag graphene nanoribbons (ZGNRs).…”
Section: Introductionmentioning
confidence: 99%
“… 23,24 In a recent study, Huang et al assayed the thermal spin-transport properties of hybrid boron, nitrogen co-doped ZGNR under various magnetic configurations. 25 In a combined experimental and theoretical study, Makarova et al ascertained the strongly coupled magnetic states at the graphene–fluorographene interface from magnetic susceptibility measurements. 26 Subsequently, Chen et al impressively demonstrated the effect of metal substrates on the local magnetic moments of zigzag graphene nanoribbons (ZGNRs).…”
Section: Introductionmentioning
confidence: 99%
“…[6] However, the AFM order in ZGNR results in zero magnetic moment and non-spin polarized transport, hindering its application to spintronic devices. Since the magnetism in ZGNRs is directly related to the spin-polarized edge states, various methods have been proposed to introduce non-zero magnetic moment by breaking the spin degeneracy of the edge states, such as substitutional doping, [10][11][12][13][14][15][16] edge functionalization with chemical groups, [17][18][19] geometric modification of the edges, [20] and external field. [21] Substitutional doping with heteroatoms such as N and B dopants is predicted to be stable at the edge, [22] which can obviously remove the spin degeneracy.…”
Section: Introductionmentioning
confidence: 99%
“…Most previous studies have been focused on the edge substitution, and the spin-polarized transport has been predicted as expected. [11][12][13][14][15][16] On the contrary, much less effort has been devoted to the far-edge substitution. [10,12,23] In most studies, an AFM coupling with broken inversion symmetry is usually supposed to be the ground state for the substitutionally doped ZGNRs, even though the energy difference between the AFM and FM states has not been carefully compared.…”
Section: Introductionmentioning
confidence: 99%